PERSEPSI ORANG TUA DALAM PROSES PEMBELAJARAN KOGNITIF ANAK USIA 4-5 TAHUN DI TK AL HIDAYAH PANGGUNGREJO - Widyawati, Nuning; Candra Nindiya, Devi; Lutfiana Rachmah, Laela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cognitive development in early childhood should ideally be stimulated through play activities, exploration, and direct experiences that are aligned with developmental stages. However, in practice, differences in understanding between schools and parents are still found, particularly in interpreting children’s learning success, which is often associated with early reading, writing, and numeracy skills. This condition has the potential to create inconsistencies in learning stimulation between home and school environments. This study aims to describe parents’ perceptions of the cognitive learning process of children aged 4–5 years at Al Hidayah Panggungrejo Kindergarten. The study used a qualitative method with a descriptive approach involving 9 parents and 1 class teacher of group A2 as research subjects. Data were gathered via participatory observation, in-depth interviews, and documentation, then analyzed interactively through data reduction, display, and conclusion drawing. The findings show that parents’ perceptions of cognitive learning tend to fall into two main directions. Some parents understand that children’s cognitive development grows through play activities, exploration, and concrete experiences. Meanwhile, others still assess learning success based on academic achievement and encourage children to take additional exercises or tutoring. This study concludes that parents’ perceptions are in a transitional stage toward a better alignment with early childhood education principles. Strengthening communication and collaboration between schools and families is necessary to ensure that cognitive stimulation develops in a consistent and optimal way.